Concepts of humans based on Behaviorism, Psychoanalysis, Humanism and Islam - Malki Ahmad Nasir, Irfan Safrudin, Rodliyah Khuzai, (Opción, 2020)
This paper aimed to reveal both the similarities and differences of the four grand theories. Using a literature study approach, this paper synthesized the four schools of thought with newly developed points of view. The results showed that the differences of the four theories were mainly on the basic psychological aspects of humans which are neutral (behaviorism), bad (psychoanalysis), kind (humanism), and pure (Islam). In conclusion, it has been implied that the development of humans is not only from the physical and cognitive aspects but also spiritual aspects which are actually their basic potentials.